Thyroglossal duct carcinoma : a case illustration - Abdullah, Kahairi; Leman, Wan Ishlah; Maria Ithaya, Rasan; Hashim, Shaharudin; Izura, Afiza; Raja Lope, Raja Ahmad (2007)
Thyroglossal duct carcinoma (TGD Ca) is a rare tumour. To date, 250 cases have been reported in the literature. The median age for TGD Ca is 40 years with few cases presenting before the age of 15 years. Most of the reported cases the diagnosis was made after surgical removal of a presumed benign thyroglossal duct cyst. Fine needle aspiration cytology is not sensitive enough to make the diagnosis. We report a case of 56 years old lady who presented with recurrent bleeding from ulcerative midline anterior neck swelling for one-year duration. There were no compressive symptoms. Diagnosis of TGD Ca was made based on trucut biopsy as well as computed tomography (CT) findings of heterogenous mass at the submental region with hyoid bone erosion. The tumour was removed together with left selective neck dissection. The surgical skin defect was reconstruct with pectoralis major myocutaneous flap. Intraoperatively, the thyroid gland was not involved. Post operatively was uneventful. The tumour histopathological examination (HPE) revealed a papillary thyroid carcinoma. From our literature review, this is the first reported TGD Ca which involved skin and requires pedicle flap reconstruction.